Modeling polymeric gels: The role of chain flexibility on the structure of physical gels - Pereyra, Rodolfo Guillermo (2017)
Using molecular dynamics simulations and a simple model for chain molecules we study the gel formation under different conditions. The main characteristic of the model is the short attractive range of the non-bonding interaction, which leads to the formation of a single percolated cluster trapped in long lived metastable state that resemble the properties of polymeric physical gels. The gels are formed by imposing a sudden quenching on well equilibrated high temperature conformations. In particular, we investigated the effect of concentration and polymer persistence length on the resulting percolated structures. Using a Monte Carlo approach, we characterize the size of the cavities that develop inside the bulk of the gels. The results show that polymers with higher persistence length produce gel structures with smaller cavities.